The Effect of Retrieval Practice on Short-Term and Long-Term Retention in HIV+ Individuals - Avci, G. (J Int Neuropsychol Soc, 2017)
OBJECTIVE: Episodic memory deficits are both common and impactful among persons infected with HIV; however, we know little about how to improve such deficits in the laboratory or in real life. Retrieval practice, by which retrieval of newly learned material improves subsequent recall more than simple restudy, is a robust memory boosting strategy that is effective in both healthy and clinical populations. In this study we investigated the benefits of retrieval practice in 52 people living with HIV and 21 seronegatives. METHOD: In a within-subjects design, all participants studied 48 verbal paired associates in 3 learning conditions: Massed-Restudy, Spaced-Restudy, and Spaced-Testing. Retention of verbal paired associates was assessed after short- (30 minutes) and long- (30 days) delay intervals. RESULTS: After a short delay, both HIV+ persons and seronegatives benefited from retrieval practice more so than massed and spaced restudy. The same pattern of results was observed specifically for HIV+ persons with clinical levels of memory impairment. The long-term retention interval data evidenced a floor effect that precluded further analysis. CONCLUSIONS: This study provides evidence that retrieval practice improves verbal episodic memory more than some other mnemonic strategies among HIV+ persons.